Tooth grafting around dental implants placed simultaneously with ridge splitting. - A/Prof Walid Elamrousy; Professor Mohamed Nassar; lecturer mohamed abdelfattah (Elsevier, 2023)
Aim or Purpose: The current study aimed to evaluate and compare the peri-implant hard and soft tissue changes after ridge splitting with simultaneous implant placement with versus without autogenous tooth graft for the treatment of horizontal alveolar ridge defects. Materials and Methods: The present study included 52 participants, aged 20 to 38, with maxillary anterior horizontal alveolar bony defects. After Kafrelsheikh University research ethics committee approval, participants were randomized into 2 groups. Control group patients underwent alveolar ridge splitting accompanied with simultaneous implant placement; whereas the study group patients underwent the same procedure, followed by autogenous tooth graft placement around dental implants. Plaque index, probing pocket depth, and pink aesthetic score were observed at 6 and 9 months after implant placement. Radiographic horizontal bone width, vertical bone level and bone density changes were assessed using CBCT at baseline, 6 and 9 months post-operatively. Results: All implants were successful and had no complications during the evaluation period. At six months, pink esthetic score and bone density in the study group were statistically significantly higher than in the control group (P<.001). At 6 and 9 months, control group showed a statistically significant loss in horizontal and vertical bone levels compared to the study group (P<.001). Conclusions: Using autogenous tooth grafts in the peri-implant bone defects after ridge splitting approach, improved the peri-implant clinical and hard tissue parameters with minimal peri-implant bone resorption, and enhanced soft tissue esthetic outcomes.As we know, this is the first study using a novel approach in alveolar ridge splitting with simultaneous implant placement and autogenous dentin graft.